Penerapan Prinsip Syar'u Man Qablana dan Bara'ah al-Ashliyah Dalam Perbankan Syariah - Lubis, Ismul Fakhri; Asmuni, Asmuni; Anggraini, Tuti (Universitas Islam Negeri Alauddin Makassar, 2023)
This research reviews the key principles of Islamic banking, namely shari'u man qablana and bara'ah al-ashliyah. The concept of shar'u man qablana emphasizes adherence to Islamic law that dates back to the time of the Prophet Muhammad, ensuring that every banking transaction and product follows religious principles. In contrast, bara'ah al-ashliyah gives freedom to financial transactions, protecting individuals and businesses from unauthorized liability, unless there is evidence to support the claim. To review this study, researchers used qualitative research methods with secondary data sources. In the context of Islamic banking, shar'u man qablana leads to the prohibition of usury and the principle of justice, creating products and services that are ethical and in accordance with Islamic law. Bara'ah al-ashliyah provides financial security, ensuring that customers are only liable for legitimate and agreed transactions. This research highlights the positive impact of implementing these two principles. In addition, these principles create a fair and ethical business environment, build customer trust, and strengthen Islamic banking's contribution to the development of an equitable society. These principles pave the way for ethical and transparent product innovation, ensuring that Islamic banking remains relevant and trusted in an ethical global economy.